Nematicidal effect of Canavalia ensiformis extract and its potentiation with nanoparticles against Meloidogyne incognita - Ceballos-Ceballos, Augusto Gil; Ochoa-Fuentes, Yisa María; Cerna-Chávez, Ernesto; Cano-García, Arely; Olalde-Portugal, Victor (Ecosistemas y Recursos Agropecuarios, 2024)
The nematicidal effect of Canavalia ensiformis seed extract combined with silicon dioxide nanoparticles was evaluated on second instar juveniles of Meloidogyne incognita, a phytopathogenic nematode that affects tomato crops. In the first experiment, concentrations of the extract were tested at 2, 4, 6, 6, 8 and 10%, observing that the most effective concentration was 10%, with 90% mortality at 24 hours. In the second experiment, concentrations of the extract at 1.5, 2.0, 2.5 and 3.0% were combined with silicon dioxide nanoparticles at 0.06, 0.08, 0.10, 0.12 and 0.14%, where the most effective was 1.5% extract with 0.14% nanoparticles, which showed a mortality of 94% at 72 hours. These results suggest that the combination of C. ensiformis extract with NP's can be a strategy for the management of M. incognita in tomato crops
Keywords: Silicium dioxide, M. incognita, mortality, treatments, combinations